Problems to keep in mind when it comes to tax reform - Fellner, William John (Washington : American Enterprise Institute for Public Policy Research, 1977)
The author agrees with many critics of the present tax structure that the provision concerning exclusion and deductions in the derivations of the personal tax base should be scrutinized periodically.
Includes bibliographical references.
aia 27/03/2019
Loans
Keywords: Income tax